Overview of Visfatin Levels in Pregnant Women as a Stunting Biomarker - Ni Nyoman Astika Dewi; Luh Putu Rinawati; Ni Putu Ditya Prabandari Dewi; I Made Krishna Paramartha; Ni Putu Intan Maha Ayu Diyanti; Aprilia Rakhmawati; Heri Setiyo Bekti (JURNAL KEBIDANAN, 2022)
Stunting is one of the malnutrition problems experienced by toddlers in the world. Indonesia is the third country in the prevalence of stunting in the Southeast Asian region. Visfatin is one of the molecules that play a role in fetal development during the womb. Reports related to visfatin in pregnant women are still very few, and mention visfatin plays a role in the incidence of preeclampsia (PE), fetal growth restriction, and gestational diabetes mellitus (GDM). This study aims to determine the level of visfatin in pregnant women as a biomarker of stunting in Bangli Regency, Bali Province. This research is a descriptive study, with an observational design. Blood samples were taken from the median cubital vein. Samples were examined by ELISA method. In the examination of vistafin levels in 30 pregnant women, the lowest level being 0.53 ng/ml and the highest level being 56.72 ng/ml. From the results obtained and compared with previous studies, the visfatin levels obtained were lower than the visfatin levels in normal pregnant women. Many studies have shown that increased levels of visfatin in maternal plasma are associated with low birth weight and intrauterine growth restriction (IUGR). Babies born with LBW have a risk of stunting.